Reformas necesarias a la ley que regula las uniones de hecho en lo concerniente al estado civil de las personas y a la protección jurídica legal de los bienes adquiridos en su vigencia. - Soto Díaz, Elina Berthila (2009)
The union in fact in the XX century, it has been considered as another form of constituting a family, the same one that is based in our moral and habit. For my personal approach it considers that the union in fact is the permanent coexistence of a man and a woman, not being indispensable for them the marriage, this makes it in order to making common life, to perpetuate the human spice, to acquire and to establish a regime of goods, but without for it is determined it a civil state. From the humanity's origin the first formation of the family was in fact by means of the union, then when laws settled down, this relationship has continued parallel to the same one, like an organization form that he/she can interpret it as irregular because it is not adjusted a model, but essentially it is structured on the same base of effects, solidary and common, differing in the formal aspects that are those of juridical character.